Working alliance in low-intensity internet-based cognitive behavioral therapy for depression in primary care in Spain: A qualitative study - Barceló-Soler, Alberto; García-Campayo, Javier; Araya, Ricardo; Doukani, Asmae; Gili, Margalida; García-Palacios, Azucena; Mayoral, Fermín; Montero-Marin, Jesus (Frontiers in Psychology, 2023)
Psychotherapies applied through the Internet have been propelled as an alternative to improve access to psychological treatments. A conceptual working alliance model of blended cognitive-behavioral therapy for depression has been developed in the UK. However, little is known about how an important therapeutic process, namely the Working Alliance, is developed and maintained in online CBT. The objective was to evaluate the validity of the WA model of b-CBT in Spanish patients with depression. 41 patients were interviewed to evaluate their experiences of an online CBT program. Interviews with participants who received a self-guided application (n=9) and who received low-intensity support (n=10), and three focus group with patients who: did not start the program (n=8), did not completed it (n=6), and who finished it (n=8) were conducted. Qualitative thematic content analysis was conducted using the constant comparative method. Analysis revealed 4 themes: ‘bond’, ‘goals’, ‘task’ and ‘usability heuristics’, which are consistent with the existing literature. A newly subcategory called ‘anonymity’ emerged, which highlights the social stigma that mental illness still has in the Spanish context. Results suggest the development and maintenance of the WA through online CBT could favor a better experience of the therapeutic process and improve the clinical impact.